2012
DOI: 10.3748/wjg.v18.i11.1176
|View full text |Cite
|
Sign up to set email alerts
|

Management of portal hypertension in children

Abstract: Portal hypertension can be caused by a wide variety of conditions. It frequently presents with bleeding from esophageal varices. The approach to acute variceal hemorrhage in children is a stepwise progression from least invasive to most invasive. Management of acute variceal bleeding is straightforward. But data on primary prophylaxis and long term management prevention of recurrent variceal bleeding in children is scarce, therefore prospective multicenter trials are needed to establish best practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 87 publications
0
41
0
4
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16] year] were identified within the study period. Gastro-oesophageal varices (n = 18) and an aortooesophageal (AO) fistula were the causes for major bleeding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10][11][12][13][14][15][16] year] were identified within the study period. Gastro-oesophageal varices (n = 18) and an aortooesophageal (AO) fistula were the causes for major bleeding.…”
Section: Resultsmentioning
confidence: 99%
“…Other sources of bleeding in PHT might include portal hypertensive gastropathy [15], gastric [16], duodenal [17] and ano-rectal varices [18]. Variceal bleeding in children is often triggered by an episode of upper respiratory tract infection, fever or aspirin ingestion [19].…”
Section: Discussionmentioning
confidence: 99%
“…Children with enlarged spleens are often first referred to a hematologist to rule out any possible hematologic processes, especially if leukopenia is present. Once hematologic causes are ruled out, referral to a pediatric gastroenterologist or hepatologist is appropriate 7. Clinical findings may include growth failure; one prospective study showed that 50% of children with EHPVO had growth retardation compared with healthy children who did not have EHPVO 5…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Normal pressure within the portal system ranges normally between 5 and 10 mm Hg 2. PHT is defined as portal venous pressure of >10 mm Hg.…”
Section: Introductionmentioning
confidence: 99%